The impact of climate variability on agricultural employment in Mexico from 1980-2017. - Karla Arlae Sánchez Guijosa; Guillermo Murray-Tortarolo; Mario Martínez Salgado (PLoS ONE)
Employment in the agricultural sector is highly dependent on climate. Most agricultural jobs worldwide rely on predictable precipitation, in terms of both quantity and seasonality. Mexico is a largely agrarian country, with at least 20 million people directly reliant on food production for the livelihoods. However, research on the relationship between climate variability and agrarian employment is limited in the nation, complicating the development of effective adaptation strategies to drought and climate change. This study aims to address this gap, by analyzing the employment changes of farmers and livestock producers at a national level in the past five decades (1980 to 2017) and its relationship to long-term precipitation variability. We employed governmental datasets from national agrarian surveys and national precipitation, both at the annual scale and seasonally within each year. We found a negative relationship between agricultural employment and total annual precipitation. In particular, employment in the livestock sector showed a negative correlation with current-year precipitation (p = 0.06, cor = -0.33), while employment in rainfed agriculture was linked to the previous year's rainfall (p = 0.07, cor = -0.33). It is likely that this pattern was driven by the positive relationship of precipitation with planted cropland area (p<0.05, cor = 0.19) and agrarian income (p<0.05, cor = 0.18). We also found that as many as 10 million people left the agrarian employments each year during the dry season. Finally, as precipitation continues to pose a challenge, it may have contributed to people of ages 23 to 35 to leave in recent years, compared to 15 and 19 in the 1990s. These findings underscore the need for national policies to mitigate the impacts of dry years on livelihoods and to inform strategies for building resilience in the agricultural sector.